Hur påverkasogräsuppkomsten av jordbearbetning? - Törnberg, David (2005)
Today it is common to spray against most weeds by using very expensive weed-killers. The goal for every farmer is to have as low costs as possible for their use of machines and weed-killers. Therefore it is in everyones interest to find other methods to fight the weeds. Finding a way to reduce the rise and growth of weeds already at the preparation of the soil would lower the number of laps over the field and also decrease the amount of weed-killing dose. Tests show that by harrow in the dark it is possible to reduce the population of weeds with up to 60%, but the normal reduction would be about 20-30%. To verify the results above we made tests by using two different methods of preparing the soil. We tested ploughing and harrowing in daylight and during night. Later we checked the number of different weeds in areas prepared in daylight and during night. By studying the results from the different methods used we found a considerable reduction of some kinds of weeds in areas prepared during night.